Biological Effects of High Radiofrequency Radiation on Wistar Rats: A Literature Review - A. Attah Timothy; Ayantunji Benjamin; Adamu Abubakar; Omede Ameh; Leleji Jeffree; Hussiani Solomon; Enemali John-Paul; Ibrahim Suleiman Zainab; Dumbiri Charity; Bwala Ishaya; Polok Caleb (Journal of Public Health International, 2022)
Aim and Objective Despite the growing concerns about the relationship between exposure to radiofrequency radiation (RFR) and detrimental health effects due to the changes in biological processes of experimental animals, there is still ongoing debate on the significance of these findings in causing significant public health problems with the growing advancement in internet technology. The aim of this study is to review existing literature on the effects of high RFR on wistar rats. Method A search was conducted on Google scholar and PubMed to identify relevant peer-reviewed articles to be included into the review. Studies eligible for inclusion included free full text articles on wistar rats exposed to ≥ 2.45GHz RFR conducted in the past 5 years. Studies included in this review were written or transcribed in English language. From 286 titles, 36 eligible studies were included in the review and assessed for quality using the Strengthening the Report of Observational Studies in Epidemiology – Veterinary Extension (STROBE-Vet) quality assessment tool. Results Studies included in this review generally had good quality (>60%) based on the STROBE-Vet assessment. This review identified numerous biological changes in wistar rats exposed to high RFR including variations in biochemical, cholinergic, genetic, histopathologic, psychological, optical, and dermatological parameters. In this review, studies identified variations in protein and liver enzymes while high RFR was found to induce oxidative stress and cellular damage of exposed wistar rats compared to the unexposed groups. This was seen in the changes in protein, lipids, enzymatic and non-enzymatic antioxidants. Studies also identified changes in expression of genes and neurotransmitters with imbalance in hormones. In addition, this review identified structural changes of cells, tissues and organs indicative of apoptosis, damage and death. Exposed rats were identified to have behavioral changes indicative of anxiety and memory decline while studies identified optical and dermatologic changes in exposed rats compared to the unexposed. Conclusion With numerous biological changes identified in wistar rats exposed to high RFR, there is an increasing risk of detrimental health events giving the advancement in internet technology and limited regulations to control exposures to RFR. Therefore, studies should be conducted to identify strategies to mitigate human exposure to RFR while policies are developed and enforced to protect human health.
Keywords: Electromagnetic Field